Comparing the efficacy and clinical outcome of telbivudine and entecavir naïve patients with hepatitis B virus‐related compensated cirrhosis. Issue 3 (March 2014) - Tsai, Ming‐Chao; Yu, Hsien‐Chung; Hung, Chao‐Hung; Lee, Chuan‐Mo; Chiu, King‐Wah; Lin, Ming‐Tzung; Tseng, Po‐Lin; Chang, Kuo‐Chin; Yen, Yi‐Hao; Chen, Chien‐Hung; Hu, Tsung‐Hui
Abstract Background and Aim There is limited data on the efficacy and outcome of telbivudine (LdT) therapy in patients with chronic hepatitis B and compensated cirrhosis. We evaluated LdT as first‐line therapy in these patients and compared with those treated with entecavir (ETV). Methods We consecutively enrolled 88 chronic hepatitis B patients with compensated cirrhosis primarily treated with LdT at least for 2 years or less than 2 years but developed resistance, and evaluated the efficacy and clinical outcomes. Meanwhile, we matched a control group who treated with ETV for comparison. Results In LdT group, alanine aminotransferase normalization (65.8%), hepatitis B e antigen seroconversion (39.8%), hepatitis B virus (HBV) DNA undetectablility (71.6%), and virologic resistance (23.9%) were noted after 2 years treatment. Compared with ETV group, there were significant difference in HBV DNA undetectablility (P < 0.001) and virologic resistance (P < 0.001). In addition, the decline of serum hepatitis B surface antigen levels, hepatocellular carcinoma development, mortality, disease progression, and the change of renal function were similar. Cox regression analysis showed that pretreatment low albumin level and high model for end‐stage liver disease scores were risk factors for disease progression. Conclusions These results indicated that although LdT and ETV are similar in clinical outcomes for patients with HBV‐related compensated cirrhosis, LdT still had lower HBV undetectablility and higher resistant rate after 2 years treatment, which was a challenge for being as first‐line therapy in these patients who need lifelong therapy.